Experimental and Theoretical Advances on Single Atom and Atomic Cluster‐Decorated Low‐Dimensional Platforms towards Superior Electrocatalysts. Issue 22 (22nd April 2022) - He, Tianwei; Puente‐Santiago, Alain R.; Xia, Shiyu; Ahsan, Md Ariful; Xu, Guobao; Luque, Rafael
Abstract: The fundamental relationship between structure and properties, which is called "structure‐property", plays a vital role in the rational designing of high‐performance catalysts for diverse electrocatalytic applications. Low‐dimensional (LD) nanomaterials, including 0D, 1D, 2D materials, combined with low‐nuclearity metal atoms, ranging from single atoms to subnanometer clusters, are currently emerging as rising star nanoarchitectures for heterogeneous catalysis due to their well‐defined active sites and unbeatable metal utilization efficiencies. In this work, a comprehensive experimental and theoretical review is provided on the recent development of single atom and atomic cluster‐decorated LD platforms towards some typical clean energy reactions, such as water‐splitting, nitrogen fixation, and carbon dioxide reduction reactions. The upmost attractive structural properties, advanced characterization techniques, and theoretical principles of these low‐nuclearity electrocatalysts as well as their applications in key electrochemical energy devices are also elegantly discussed. Abstract : Low‐dimensional (LD) nanomaterials, including 0D, 1D, 2D nanomaterials, combined with low‐nuclearity metal atoms, ranging from single atoms to subnanometer clusters, are becoming rising star heterostructures for a myriad of electrocatalytic reactions. In this review, the most attractive structural and theoretical features of these nanoheterostructure electrocatalysts, together with their key applications toward the fabrication of energy‐related devices, are comprehensibly addressed.